Comparative study on NO2 and H2S sensing mechanisms of gas sensors based on WS2 nanosheets - Liu, Di; Tang, Zilong; Zhang, Zhongtai (Sensors and actuators. B, Chemical, 2020)
•WS2 nanosheets with edge size about 10 nm were synthesized by the sulfurization of the WO3 nanomesh.•The sensor based on WS2 nanosheets exhibited p-type sensing properties and excellent selectivity to NO2 gas at a low temperature of 160 °C.•The different sensing mechanisms of WS2 nanosheets for NO2 and H2S sensing were proposed based on the experimental results. Due to their high intrinsic conductivity and narrow band gap, nanostructured metal sulfides have attracted considerable attention as promising gas sensing materials. Here, we report the WS2 nanosheets with edge size only about 10 nm synthesized by sulfurization of the WO3 nanomesh. The WS2 nanosheets exhibit p-type sensing characteristics and excellent selectivity to NO2 at a low temperature of 160 °C, which can be attributed to the strong physical affinity of the WS2 nanosheets to the NO2 gas molecules. Importantly, by designing sensing experiments under different background gases, we found that WS2 nanosheets do not require oxygen for NO2 sensing, while oxygen is required for H2S sensing. Therefore, based on the adsorption and desorption and charge transfer between WS2 nanosheets and adsorbed gas molecules, we propose different sensing mechanisms of WS2 nanosheets for NO2 and H2S sensing.